Educational tools for the teaching of a foreign language in virtual environments - Guevara Barahona, Eduardo Moisés; Rivera de Martínez, Susana Raquel; Vigil Flores, Hector Alonso (2024)
The present report is about a specialization course that took pace during COVID-19 pandemic. The main purpose was that of specializing future graduates to develop online teaching-learning processes of foreign languages. The specialization course was divided into three modules. Each module lasted eight weeks. They covered theoretical, practical, and functional contents to set up a virtual classroom making use of several educational applications such as Moodle, Google Classroom (asynchronous activities), platforms like teams,Meet, zoom (synchronous activities). The report also presents the objectives, the learning results that students got. One of the most important achievements was the experience of designing educational material for virtual classrooms in the Learning Management System available on the internet, such as: podcasts, interactive images, videos, google websites, games, tests, and quizzes, among others.